Protocol for resilience of degraded Vertisol with field level validation - KUNDU, S.; COUMAR, M. VASSANDA ,; SAHA1, J. K.; ADHIKARI, TAPAN ,; RAJENDIRAN, S.; PATRA, A. K. (Journal of Soil and Water Conservation, 2021)
A research investigation was carried out in the farmer’s fields to study resilience capacity of degraded Vertisols of AESR 10.1. Field experiments were conducted on 10 farmer’s fields which were selected based on soil quality index (SQI) values ranging from low to high. Each of the ten identified sites was amended with wood charcoal @ 0, 5.4, 10.8 and 16.2 t ha-1 at the time of land preparation before sowing of soybean crop. Thereafter, soybean followed by wheat crop was raised and yields were recorded. After the harvesting of wheat crop, soil samples were collected and analyzed for quantity values of the key soil quality indicators. Based on quantitative values of the key indicators, SQI were computed for all the interventions at ten sites. The resilience index (RI) of the soils of each site due to application of charcoal @ 5.4 t ha-1 (I1), 10.8 t ha-1 (I2) and 16.2 t ha-1 (I3) was computed. The result showed that the loss of soil quality as compared to respective pristine soil are different in different sites and the values ranged between 0.114 unit to as high as 0.650 unit. After imposition of interventions, there was improvement in SQI values at each site, however, magnitude of improvement in SQI value varied from site to site. Under intervention I1 (5.4 t ha-1), I2 (10.8 t ha-1) and I3 (16.2 t ha-1) the improvement in SQI values ranged from 0.026 unit to 0.246 unit , 0.051 unit to 0.287 unit and 0.067 unit to 0.392 unit, respectively. It was further observed that out of the ten sites the value of resilience index ranged from 28.12 to 68.78% which resulted in gain in soybean yield from 264 to 442 kg ha-1 and gain in succeeding wheat yield from 103 to 815 kg ha-1. The soil analysis carried out after the harvest of wheat crop showed that out of the eight key indicators identified for vertisol, only two indicators, namely, TOC and Alkaline Phosphatase activity showed significant improvement due to application of wood charcoal. Also, significant improvement in microbial biomass C content in the soil was observed due to charcoal application. Thus, the developed protocol for measuring soil resilience can be successfully used to measure the resilience capacity of degraded vertisols in response to management interventions.